117 The divergent effects of IGFBP1 and IGFBP2 on vascular endothelial function. (June 2018) - Slater, Tom; Bruns, Alexander-Francisco; Wheatcroft, Stephen
Abstract : Introduction: Insulin like growth factor binding proteins(IGFBP) have cellular effects extending far beyond binding and transport of insulin like growth factors(IGF). Our group showed that global overexpression of IGFBP1 in mice increased insulin sensitivity and endothelial nitric oxide generation, leading to reduced blood pressure and reduced atherosclerosis. These actions were independent of IGF and thought to be induced by interaction between the RGD domain of IGFBP1 and integrins, with subsequent up-regulation of the Akt pathway. Low IGFBP2 levels are associated with obesity and insulin resistance in humans, and our group found that global overexpression of IGFBP2 in mice improved insulin sensitivity and protected against dietary obesity. IGFBP2 has been associated with increased angiogenesis in cancer, but potential vasomotor effects remain unstudied. Given the structural similarities between IGFBP1 and IGFBP2, we hypothesised that over expression of IGFBP2 may enhance endothelial function in a similar fashion to IGFBP1. To test this, we investigated vascular function in mice with global human IGFBP2 over expression and in a novel model of tamoxifen-inducible selective endothelial overexpression of IGFBP2. Methods: Global hIGFBP2 expressing mice were purchased from Jax Laboratories. Cre-lox recombination was used to create hIGFBP2 inducible mice. Briefly, this involved the creation of a transgenic mice with cDNA encoding hIGFBP2 but with a floxed stop codon preventing transcription. These were bred with VE-Cad-ERT-Cre mice. When these mice were injected with tamoxifen at 7–8 weeks, the Cre recombinase is activated, cleaving the stop codon and allowing the transcription of IGFBP2 in the endothelium alone. Rings of thoracic aorta from 12–13 week old mice were examined in an 8-channel organ bath. After ensuring Viability with potassium chloride, vasodilation and vasoconstriction were studied with ascending concentrations of acetylcholine (Ach) and phenylephrine (PE). NO production was assessed by blocking NOS with L-NMMA. Sodium nitroprusside (SNP) was used to assess endothelium independent vasodilation. Results: Overexpression of IGFBP2 was confirmed in the endothelium of both mouse strains, significantly more markedly in the endothelium specific mice. In contrast to our findings with IGFBP1, neither global nor EC-specific overexpression of IGFBP2 led to any significant difference in responses to Ach, PE or SNP. Basal NO generation was unchanged in hIGFBP2 mice. Conclusions/Implications: Despite structural similarities, proangiogenic properties and favourable metabolic effects, there is no evidence currently of any enhancement in endothelial function when IGFBP2 is over expressed. This may be due to competitive actions of different IGFBP2 binding sites, leading to a net neutral effect. Further investigation is required to elucidate these mechanisms of action, as well as examining the effect of IGFBP2 on endothelial function in a pathological state, such as obesity induced insulin resistance or STZ induced diabetes.